Students Existential Experience in Developing Environmental and Energy Awareness for Education for Sustainable Development at MAN 2 Pamekasan - Yuliyana Sintiya; Shinta Oktafiana (Entita: Jurnal Pendidikan Ilmu Pengetahuan Sosial dan Ilmu-Ilmu Sosial, 2026)
Ecological awareness is an attitude and action in maintaining and preventing environmental damage that is formed through existential experiences from involvement in environmental awareness activities, such as planting, plant care, environmental clean-up actions, and scientific paper competitions. This study aims to describe the existential experiences of students in the Manpala Naviri nature lover extracurricular activities of MAN 2 Pamekasan. This study uses a qualitative method with a phenomenological approach, with the subject being the members of the extracurricular. Data collection techniques are carried out through observation, interviews, and documentation. The results of the study show that students' existential experiences are formed through direct involvement in environmental activities and are interpreted through four dimensions, namely the body experienced through activities, direct involvement of the body and emotions in activities, experienced time includes how long the activity is carried out, experienced space refers to the place used in activities which in this study are known to be the school environment space of MAN 2 Pamekasan and the coast, and experienced human relations which are relationships between humans that arise through interactions in activities.